Fisherman Society Kinship Systems in Talisayan Village District of Talisayan, Berau (Jurnal Pembangunan Perikanan dan Agribisnis, 2019)
The purpose of this study were identify the social background of fishermen community, especially the kinship structure, marriage and inheritance patterns, to identify  the role of kinship systems in managing fishery resources. This research applied purposive sampling method with the number of respondents were 30 people (composed from 5 nuclear families and 5 extended families of Bugisnese, 5 nuclear families and 5 extended families of Mandarnese, 5 nuclear families and 5 extended families of Beraunese). This research was conducted in June 2018 to February 2019. Data analyzed based on genealogical Analysis and then presented descriptively. The results showed that: Kinship term used by nuclear and extended families on Bugisnese, Mandarnese and Beraunese fishermen to greet the families members in daily activities. Kinship structure of nuclear and extended families of Bugisnese, Mandarnese and Beraunese formed by patrilineal system.  Marriage patterns of nuclear and extended families on Bugisnese, Mandarnese and Beraunese fishermen adjust the customs and habits of each ethnic. Family inheritance patterns of nuclear and extended family on Bugisnese, Mandarnese and Beraunese adopted the individual and collective inheritance system where men received boat or fishing gear women received house or land. The role of the kinship systems families on Bugisnese, Mandarnese and Beraunese fishermen was to determine the co-operation mechanism on fishermen community based in Talisayan village on Common Pool Resources (CPR) system.